Performance evaluation of nitrogen for fire safety application in aircraft - Dinesh, Akhil; Benson, C. M.; Holborn, Paul; Sampath, Suresh; Xiong, Yifang (Elsevier, 2020)
Fire suppression is an important safety certification requirement for aircraft as it is for all safety critical systems. Risk analyses are required at the design and certification stages to determine the probabilities and means of mitigating such risks. [18] shows an approach for spacecraft, [19] for passenger ships and [30] for reactors. An important analysis tool for aircraft is the Zonal Analysis process [31]. Such analyses include investigation of means of fire suppression for which the use of Halon 1301 was a popular choice. The production of Halon and several halocarbons were banned under the Montreal Protocol in 1994, which necessitates an investigation for use of environmental-friendly agents for this application. The primary objective of this paper is to determine the ‘design concentration’1 of nitrogen required for fire suppression. Computational Fluid Dynamics (CFD), in combination with experimental verification is described in this paper. The air flow rate in the cup-burner model was varied between 10 L/min and 40 L/min for a low-speed numerical model and was validated against the BS ISO 14520 cup burner test [1] to determine the extinguishing concentration of nitrogen. The study revealed that the design concentration of nitrogen was 34% (14% oxygen concentration). Further investigation suggested that at low air flow rates (10L/min and 20 L/min case), distortions produced in the flow led to erroneous measurement of oxygen concentration in experiments. The fire suppression model was extended to an n-heptane pool fire in a large enclosure. The recorded design concentration was approximately 39% additional nitrogen corresponding to 13% oxygen concentration by volume. It was observed that the weight of nitrogen required increased by 7.5 times compared to Halon 1301 use for this model. Future work can be explored in aircraft cargo and engine bay fire safety systems through Minimum Performance Standard (MPS) testing and simulations with nitrogen as the agent. Such work will feed directly into system safety assessments during the early design stages, where analyses must precede testing.
Keywords: Design concentration; Computational Fluid Dynamics; Cup-burner test; Minimum performance standard; Fire extinguishing